Analisis Faktor-faktor yang Mempengaruhi Pemilihan Moda Transportasi Menuju Kampus Oleh Mahasiswa Geografi Universitas Negeri Jakarta - ivanya putri; Amanda Azra Salsabhila; Najma Alifia; Lia Marliana; Muhammad Farrel Ardiansyah; Ode Sofyan Hardi (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Jakarta, 2026)
This study aims to analyze the factors influencing the choice of transportation mode to campus by students of the Geography Study Program at Jakarta State University. This study was conducted at Jakarta State University using a descriptive quantitative approach and spatial analysis. Primary data were obtained through questionnaires distributed to students, while secondary data were obtained through literature review. Spatial analysis was conducted using buffer and hotspot analysis to observe the distribution patterns of student residences and transportation mode use. The results showed that most students live in East Jakarta and the Greater Jakarta buffer zone with a distance of more than 20 km to campus. All respondents used public transportation, with Transjakarta as the most dominant mode, followed by KRL (Commuter Line) and online motorcycle taxis. Cost was the primary consideration in transportation mode choice, followed by convenience and availability, while travel time and comfort had a relatively smaller influence. These findings indicate that student transportation mode choice is influenced by the interaction between distance, cost, and accessibility of the urban transportation network. This research is expected to be a consideration in campus transportation planning and the development of a more integrated and sustainable public transportation system.